Gender and competition: Evidence from jumping competitions - René Böheim; Mario Lackner (Institute for the Study of Labor (IZA), 2013)
We analyze if female athletes differ from male athletes in their competitive behavior, using data from high jump and pole vault competitions. We estimate if female athletes use risky strategies as often as male athletes and whether or not their returns to risky strategies differ. Returns to risky strategies are identified via an instrumental variable approach where we use other athletes' declarations as instruments for individual risk taking. We find that women use risky strategies less often than men, although their returns are significantly greater than men's. We also find that women's returns to risky strategies do not differ between relatively low and relatively high risk situations, whereas male athletes' returns decrease in the level of risk. Our results show considerable differences between male and female professional athletes which are likely to be a lower bound of overall gender differences in risk-taking behavior.
Keywords: J16; D81; 330; competition; gender differences; risk preferences